planning and design of a tourist village in the marshes of southern Iraq - الملاحويش, أ.د.لؤي طه محمد رشيد; الهاشمي, علياء علي حسين (Journal of Planner and Development, 2012)
This study analyzes how to make use of the resources in the marshlands of Iraq and how to utilize them, especially after the water returns to these areas and they are revitalized. We take an example of AL- Saheen Marsh and plan an ideal tourist resort there. This example can further expand to include other parts of the marshlands. The resort will utilize the local environment and tourist characteristics as it will have a feel and architectural resemblance to the houses and buildings that are currently built there. In addition the transportation methods will be the same as those used by the locals. Yet the resort will still posses all the facilities required by a modern tourist resort that includes all the services that will make the guest comfortable. Through this resort there will be a movement of Arab and foreign tourists that will result in an exchange of cultures. The tourist will be introduced to the culture of the area and will commence in the various local activities. That , in addition to the apparent immense financial advantages of this project that will have a considerable returns for the area and the country as a whole. It will also employ a considerable number of local people hence reducing the unemployment rate in that area in addition to the social and economic advantages for the marshland society.